Delayed Post-Traumatic Fronto-Ethmoidal Sinus Mucocele Evaluated with Short and Long TE MR Spectroscopy. Issue 6 (December 2013) - Aghakhanyan, Gayane; Lupi, Giancarlo; Frijia, Francesca; Hana, Hlavata; Lombardo, Francesco; De Cori, Sara; Canapicchi, Raffaello; Vannozzi, Riccardo; Montanaro, Domenico
Mucoceles are slow-growing, benign, expansile, mucoid-filled masses developing after obstruction of the sinus ostium. Late post-traumatic mucoceles are relatively rare entities and the literature is limited to single case reports. We describe an unusual case of post-traumatic frontoethmoidal mucocele, evaluated with computed tomography (CT), magnetic resonance imaging (MRI) and proton MR-spectroscopy ( 1 H-MRS). As a contribution to the diagnostic work-up of the mucocele, 1 H-MRS demonstrates a dominant peak at 2.0 ppm at long echo time (TE) and an additional component at 3.8 ppm at short TE due to mucus glycoprotein compounds of the mucocele.